An Investigation Of The Use Of Water Elements In Historical Places: Vis-A-Vis Basic Design Criteria, Ottoman Period - Koray, Goksu; Erdoğan, Gülsüm Sıla; Güven, Mustafa (BBDS - Black Book: Drawing and Sketching, 2023)
This study aimed to thoroughly investigate the water elements used with the architecture of the Ottoman Period vis-a-vis the basic design criteria, from the building and garden scale to the open spaces scale in squares. The use of water elements in the Ottoman Empire was not only remarkable due to intrinsic design features and details; but also, thanks to universal design values of the period inherited from other civilizations, as a matter-of-fact water element has always been one of the focal points of the discipline of architecture throughout history. The water elements, including fountains, mosque fountains, decorative pools, public fountains, and square fountains built by architects during the Ottoman period were investigated within the scope of this study vis-a-vis the basic design criteria, considering the period of construction and all the elements that helped constitute the building identity. The water elements in question included Kaptan-? Derya Sadrazam Hüsrev Mehmed Pasha Fountain, Gazanfer Agha Fountain, decorative pool in Topkap? Palace, Ahmet III Fountain, Hüma?ah Hatun Fountain, the ornamental pool in Hasbahçe, the Hagia Sophia fountain, and the Hagia Sophia trihedral fountain. The research methodology was based on literature review using the Google database. Eight different examples from the Ottoman period that survived until today were selected, and on-site discovery, observation, and photography activities were carried out for the investigation in the scope of the study. As a result of the study, it was seen that the eight examples met the basic design criteria in terms of color, texture, material, and scale. In the context thereof, the examples featured similar design characteristics. Furthermore, there were functional differences depending on the location of the architectural water elements.